Effects of AlN inorganic binder on the properties of porous Si3N4 ceramics prepared by selective laser sintering. Issue 20 (15th October 2022) - Wu, Ya-Ru; He, Jun-Hong; Cheng, Li-Jin; Wu, Jia-Min; Shi, Yu-Sheng
Abstract: Porous Si3 N4 ceramics are widely used in the aerospace field due to its lightweight, high-strength, and high wave transmission. Traditional manufacturing methods are difficult to fabricate complex structural and functional ceramic parts. In this paper, selective laser sintering (SLS) technology was applied to prepare porous Si3 N4 ceramics using AlN as an inorganic binder. And the effects of AlN content on the properties of the obtained ceramic samples were explored. As the AlN content increased, nano-Al2 O3 and nano-SiO2 formed the eutectic liquid phase, enhancing the sintering densification and phase transformation of Si3 N4 poly-hollow microspheres (PHMs). The island-like partial densification structures in Si3 N4 green bodies increased. During the high-temperature sintering, the eutectic liquid phase partially transformed into the mullite phase or reacted with AlN and Si3 N4 to form the Sialon phase. With the increase of AlN content, the fracture mode of Si3 N4 ceramics changed from fracturing along PHMs to fracturing across PHMs. The bonding depth between PHMs increased and the connection between the grains was tighter, so the Si3 N4 ceramics became denser. With the increase of AlN addition, the total porosity of the porous Si3 N4 ceramics tended to decrease and the flexural strength gradually increased. When AlN content was 20 wt%, the total porosity and the flexural strength were 33.6% and 23.9 MPa, respectively. The addition of AlN inorganic binder was carried out to develop a novel way to prepare high-performance porous Si3 N4 ceramics by SLS.